Inventive methods of vaccine development: Research of optimal conditions of photodynamic inactivation - Melentieva, Khristina; Martynov, Artur; Kalinichenko, Svitlana; Antusheva, Tetyana; Ovetchyn, Petro (Annals of Mechnikov’s Institute, 2023)
Introduction. This topic concerns the development of hypoallergenic and non-reactogenic vaccines of the latest class, which will contribute to the creation of population immunity against many infectious diseases in all WHO identified 3 priority directions for replacing parenteral vaccines with non-parenteral ones, which are based on the ability of antigens to penetrate through mucous membranes. The most promising of them are mucosal vaccines, the use of which allows you to ensure the continuity of the antigenic stimulus and maintain a high level of collective immunity against infections managed by means of specific prevention, including COVID-19. Recently, the situation in our country regarding managed infectious diseases, both bacterial and viral, has significantly worsened and is becoming even more urgent, since large-scale hostilities in our country are accompanied by the deterioration of sanitary conditions, significant migration processes among the population of Ukraine, the accumulation of refugees in premises, the destruction of water mains, a large number of wounded servicemen and civilians who need urgent medical assistance in the field. All over the world, to reduce infectious diseases, a system of measures is widely used to prevent, limit the spread and eliminate infectious diseases. One of these means is vaccine prophylaxis. Certain problems arise in the development of vaccine preparations. For example, the spontaneous emergence of pathogenic properties, the ability to reverse attenuated strains of microorganisms, which can cause disease. Inactivated vaccines do not require strict storage and transportation conditions, so they are more attractive for the pharmaceutical industry. That is why the search for compounds and methods for inactivating pathogens that would not form covalent bonds with the antigen, thereby increasing their reactogenicity and allergenicity, is extremely necessary. At this time, it has been established that pathogen inactivation systems (SP) in blood products are effective against numerous bacteria, viruses, and parasites and are widely used in blood product decontamination technologies in transfusion medicine. These premises gave us the idea of ​​extrapolating the experience of transfusionists in photodynamic inactivation of blood products to vaccinology with the aim of replacing inactivators/preservatives with non-toxic metabolic photoinactivation agents that do not require vaccine purification and do not form covalent bonds with vaccine antigens. Materials and methods. scientific review and practical research articles, information from the WHO database. Results and discussion. The task of researchers at this time is to eliminate shortcomings in the production of vaccine preparations by preventing the formation of covalent bonds between the modifier and the antigen - the target - toxin or pathogen. At the same time, inactivation should remain very effective. It is known that riboflavin is an activator of cellular metabolism in humans and animals, but in addition to its key role, it acts as a photosensitizer and is used in disinfection systems, which provides an antimicrobial effect. The disinfection method that uses a photosensitizer is called antimicrobial photodynamic therapy. Antimicrobial photodynamic therapy (aPDT) is a promising approach for of pathogens in blood and blood derivatives. The advantage of antimicrobial photodynamic therapy is that there are no resistant strains to it. And the main task today is to choose the most optimal methods and conditions for finding the best methods and substances for them during photodynamic inactivation. These studies will allow us to understand the predictability and perspective of replacing covalent inactivators with means of photodynamic inactivation of bacteria in vaccinology with the aim of further implementation in the development of new classes of non-toxic and non-allergenic vaccines. Key words: antimicrobial photodynamic therapy, photoinactivation, riboflavin, vaccines